Deus ex-machina: forme contemporanee del credere nel relativo - Pace, Enzo (Incontri. Rivista europea di studi italiani, 2020)
Deus ex-machina Modern Form of Believing in the Relative Secularization continues to produce its effects over the long term, despite the conspicuous recovery of public space regained from 1980 to today by the major world religions. The alleged return of the sacred or the alleged revenge of God, however, does not seem able to contrast the triumph of capitalism as a religion, to take up the formula used by Walter Benjamin. The modern consumer society saves the salvable, incorporating the sacred into the commodities, making the goods a sign of identification, a cult. The appearance of strong religions, so-called fundamentalisms, constitutes a specular and high response to the forms of believing in the relative in the societies of late secularization. The author starts from the prophetic visions on the magnificent fortunes of capitalism, advanced by Max Weber and Walter Benjamin, analyzing the process of commodification of religious symbols in contemporary affluent societies. Therefore, there is not the return of God who was presumed dead. Rather the machine of neo-capitalism saves God by making him prodigiously incarnate in the beauty of goods.